Budgetary Control System in India: An Overview: The Role of Budgetary Control in India's Welfare Program (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The term Budget comes from the French word 'BOUGETTE' meaning 'leather bag.' or 'sack’ or ‘pouch’. According to the British legacy, India's Union budget has been submitted in accordance with the British Budget on the last working day of February. In 2001, the Finance Minister then presented this report to the House. This was stopped. Every year, on the last working day in February, the Minister of Finance of India presents the Union Budget of India (General Budget).The term budget is not used in the Indian Constitution but AFS (Annual Financial Statements) which shows government receives and payments under three parts where government accounts are kept- In the Indian ConstitutionConsolidated Fund, Public Account and Contingency Fund. Financial jargon for managing revenue and spending is budgetary control. In practise, this means regularly comparing actual revenue or expenditure with planned revenue or expenditure in order to determine whether corrective action is needed or not. Comparing budgets with actual operational results is referred to as budgetary control. Such budget control supports departmental planning, coordination, decision-making, operational results monitoring and employee motivation towards business targets. Budgetary control is the cycle through which budgets are ready for the future time frame and contrasted with the real exhibition, to recognize fluctuations where proper. The compare of estimates with actual figures will help the management to detect differences and to take immediate corrective measures. In India the Budget plays an important role for making Policies of Welfare Programme for the development of poor and needy people.